Analysis Of The Determinants Of The Growth And Development Of Bumdes Karya Maju Cemerlang In Apung Village, Tanjung Selor District, Bulungan Regency, North Kalimantan, Indonesia - Silva Septriana; Rosmayati, Siti (Yayasan Azka Hafidz Maulana, 2025)
Village-Owned Enterprises (BUMDes) are one of the important instruments in building the economy at the village level. This study aims to analyze the determinant factors that affect the growth and development of BUMDes Karya Maju Cemerlang with a qualitative approach. Through observation, interviews and documentation studies on BUMDes Karya Maju Cemerlang, it was found that leadership factors, community participation, government policies, and access to resources are the main factors that determine the success of BUMDes. This article provides insight into the importance of synergy between Stakeholders to increase the role of BUMDes in sustainable village development